MYRAFF 2.0: Arabic educational E-games - Hashim, Marzidah; Saleh, Hanan; Muhammad, Norasmazura; Raja Sulaiman, Raja Munirah; Salleh, Nellia Lizrina (Centre for Teaching and Learning (CTL) and International Islamic University Malaysia (IIUM), 2018)
Learning Arabic as a foreign language requires a lot of continuous practice and memorization. Teachers who are teaching Arabic for non-native speakers usually will provide students with numerous exercises and notes to ensure that students will continually engage themselves with the subject at home. Previously, these exercises and notes were delivered in the form of photocopied version. Nonetheless, teachers have now started to digitalise their notes and exercises. While this new improvement is more interesting and engaging, it requires more preparation time. The teachers also need to have some basic IT skills and adapt to the rapid changes in technology which can be tedious to some. MyRaff 2.0 is one of the platforms that offers a solution to this problem. This invention offers a collection of Arabic educational egames created using PowerPoint Visual Basic for Application (VBA) code, triggers and advanced animation. The games offered vary from simple card games to complex crime solving games. All games are creatively designed to make players learn Arabic in a fun and enjoyable way.